Decision Supplier Package System Using Fuzzy Subjective and Objective Integrated Weights Method (case Study: PT Garudafood Putra Putri Jaya) - Muhammad Saiful Irawan; Rifki Fahrial Zainal; Syariful Alim (JEECS (Journal of Electrical Engineering and Computer Sciences), 2017)
The purchasing department is the part that plays an important and influential role in a company even can be said mostof the business process comes from this section. Because of its nature as a procurement of goods and services then oneof its duties and responsibilities is to choose suppliers of procurement of goods and services for production operationalprocesses within the company. In this case PT Garudafood Putra - Putri Jaya often have difficulty in determining thebest product packaging supplier because of the performance instability of each supplier. For that the company needsa system whose purpose is to help decide the best supplier determination. Decision support system is a computer-basedinformation system that generates various decision alternatives to assist management in handling various structuredor unstructured problems using data or models. There are many methods used in a decision support system such asFuzzy Subjective And Objective Integrated Weights. Fuzzy can solve the problem of uncertainty in determining theweight of each supplier's criteria. The result of the implementation of this decision support system resulted in thesupplier of Mandhara Adhitama Utama as the best supplier. Where the results of calculations with Fuzzy SubjectiveAnd Objective Integrated Weights this supplier obtained the highest value with the number 1.742.